2020
DOI: 10.1016/j.urology.2020.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Resident-Driven Holistic Lean Daily Management System to Enhance Care Experience at a Safety Net Hospital

Abstract: OBJECTIVE To describe the use of Lean in urology at Zuckerberg San Francisco General, a community safetynet and trauma hospital that serves as a major teaching site for the University of California San Francisco. METHODS We examined our process improvement activities from 2016 to 2018. Our Lean Daily Management System (DMS) includes a 15-minute team huddle ("urology Lean work") of service residents, faculty, clinic and operating room nursing staff, and anesthesia liaisons. Our DMS also includes a 5minute preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In a 2020 article, Tortorella et al, 15 studying how Lean leader behavior changes over time with Lean implementation in a single hospital, reported a statistically significant increase in both task-oriented behaviors (such as visiting the work floor, exchanging information, formulating and communicating goals and objectives, and monitoring and evaluating) and relationship-oriented behaviors (such as, demonstrating commitment and support, creating a learning environment, and empowering employees) in hospital leaders between June 2017 and July 2018. Tresh et al 26 reported on the engagement of residents in quality and safety improvements through participation in a Lean DMS over a 2-year period at Zuckerberg San Francisco General Hospital. Among the improvement results reported were reduced pediatric urology clinic new-patient access time from 119 days to 21 days and reduction in Bacillus Calmette-Guerin treatment time from 180 minutes to 105 minutes.…”
Section: Quantitative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2020 article, Tortorella et al, 15 studying how Lean leader behavior changes over time with Lean implementation in a single hospital, reported a statistically significant increase in both task-oriented behaviors (such as visiting the work floor, exchanging information, formulating and communicating goals and objectives, and monitoring and evaluating) and relationship-oriented behaviors (such as, demonstrating commitment and support, creating a learning environment, and empowering employees) in hospital leaders between June 2017 and July 2018. Tresh et al 26 reported on the engagement of residents in quality and safety improvements through participation in a Lean DMS over a 2-year period at Zuckerberg San Francisco General Hospital. Among the improvement results reported were reduced pediatric urology clinic new-patient access time from 119 days to 21 days and reduction in Bacillus Calmette-Guerin treatment time from 180 minutes to 105 minutes.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…In the 2020 data pull, Tresh et al 26 reported on a urology team implementation of daily accountability huddles to review and improve operational metrics in the clinic setting and the perioperative setting. Mate et al 27 described "carefully scripted" weekly huddles to review performance data for the week and Cromwell et al 28 reported implementation of weekly huddles at the whiteboard located outside of the department chief's office to drive accountability for improved autopsy turnaround time (TAT).…”
Section: Daily Accountabilitymentioning
confidence: 99%
“…[1][2][3][4][5][6] While the studies may be limited, other residency programs have also shown similar results and have led to increased involvement of residents in other quality initiatives. 8 The thought is that the success of Lean is attributed to the ability to identify the issues needing immediate assistance and provide suggestions for improvement in real time. 5 Throughout an academic year (July through June), it is expected that resident trainees continue to develop skills and improve their performance with time management.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its reported successes in many areas important to patient care, [1][2][3][4][5][6]8 Lean management was hypothesized to help achieve decreased wait times and increased utilization of OMT in patient visits. It was also thought that data from this study could assist other osteopathic recognized family medicine residency clinics in improving efficiency and enhancing time organization for better patient care.…”
Section: Aim #3mentioning
confidence: 99%
“…The Japanese Society of Quality Control (JSQC) describes daily management as activities required to effectively achieve organizational objectives with regard to the job performed by each unit in the organization (JSQC, 2014). It is a system that documents the processes related to a particular job, as well as plans for managing and improving the operation (Cassidy, 1996), and daily management is practiced in the industrial (Ohno and Bodek, 1988;Kennedy, 2019) and service sectors (Biskupska and Chandima Ratnayake, 2019;Ontengco, 2019;Wang et al, 2019;Tresh et al, 2020).…”
Section: Management Based On Student Scoresmentioning
confidence: 99%